Extended vs Short-term Buprenorphine-Naloxone for Treatment of Opioid-Addicted Youth: A Randomized Trial - Woody, George E. (2008)
CONTEXT: The usual treatment for opioid-addicted youth is detoxification and counseling. Extended medication-assisted therapy may be more helpful. OBJECTIVE: To evaluate the efficacy of continuing buprenorphine-naloxone for 12 weeks vs detoxification for opioid-addicted youth. DESIGN, SETTING, AND PATIENTS: Clinical trial at 6 community programs from July 2003 to December 2006 including 152 patients aged 15 to 21 years who were randomized to 12 weeks of buprenorphine-naloxone or a 14-day taper (detox). INTERVENTIONS: Patients in the 12-week buprenorphine-naloxone group were prescribed up to 24 mg per day for 9 weeks and then tapered to week 12; patients in the detox group were prescribed up to 14 mg per day and then tapered to day 14. All were offered weekly individual and group counseling. MAIN OUTCOME MEASURE: Opioid-positive urine test result at weeks 4, 8, and 12. RESULTS: The number of patients younger than 18 years was too small to analyze separately, but overall, patients in the detox group had higher proportions of opioid-positive urine test results at weeks 4 and 8 but not at week 12 ( [Formula: see text] = 4.93, P = .09). At week 4, 59 detox patients had positive results (61%; 95% confidence interval [CI] = 47%-75%) vs 58 12-week buprenorphine-naloxone patients (26%; 95% CI = 14%-38%). At week 8, 53 detox patients had positive results (54%; 95% CI = 38%-70%) vs 52 12-week buprenorphine-naloxone patients (23%; 95% CI = 11%-35%). At week 12, 53 detox patients had positive results (51%; 95% CI = 35%-67%) vs 49 12-week buprenorphine-naloxone patients (43%; 95% CI = 29%-57%). By week 12, 16 of 78 detox patients (20.5%) remained in treatment vs 52 of 74 12-week buprenorphine-naloxone patients (70%; [Formula: see text] = 32.90, P < .001). During weeks 1 through 12, patients in the 12-week buprenorphine-naloxone group reported less opioid use ( [Formula: see text] = 18.45, P < .001), less injecting ( [Formula: see text] = 6.00, P = .01), and less nonstudy addiction treatment ( [Formula: see text] = 25.82, P < .001). High levels of opioid use occurred in both groups at follow-up. Four of 83 patients who tested negative for hepatitis C at baseline were positive for hepatitis C at week 12. CONCLUSIONS: Continuing treatment with buprenorphine-naloxone improved outcome compared with short-term detoxification. Further research is necessary to assess the efficacy and safety of longer-term treatment with buprenorphine for young individuals with opioid dependence.